Robust fault reconstruction for a class of infinitely unobservable descriptor systems. Issue 8 (11th June 2017) - Chan, Joseph Chang Lun; Tan, Chee Pin; Trinh, Hieu
ABSTRACT: This paper presents a robust fault reconstruction scheme for a class of infinitely unobservable descriptor systems using sliding-mode observers, which improves on previous work that do not consider robustness in fault reconstruction or are applicable only for infinitely observable systems. By removing certain states and treating them as unknown inputs, a reduced-order system that is infinitely observable and compatible with existing sliding-mode observer schemes is created. A sliding-mode observer is used to estimate the states of the reduced-order system and reconstruct the fault. The existence conditions for the scheme in terms of the original system matrices are investigated and presented. Linear matrix inequality techniques are used to minimise the effect of disturbances on the fault reconstruction. Finally, a simulation is carried out and the results verify the efficacy of the proposed scheme.